Neuroferritinopathy: missense mutation in FTL causing early-onset bilateral pallidal involvement - Maciel, P. (2005)
The authors identified a missense mutation in the FTL gene (474G>A; A96T) in a 19-year-old man with parkinsonism, ataxia, corticospinal signs, mild nonprogressive cognitive deficit, and episodic psychosis. This mutation was also present in his asymptomatic mother and younger brother, who had abnormally low levels of ferritin in the serum. The patient and his mother displayed bilateral involvement of the pallidum.